Analisis Pembelajaran Abad 21 dalam Landasan Pesantren Spirit but Modern System di Ma'had Al-Zaytun, Indramayu - Imam Prawoto; Dewi Nopasari; Nazma Aliya Mutia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
21st Century Learning is an educational concept that focuses on developing students' skills to achieve success which is influenced by technology, information and globalization. Islamic boarding schools are educational institutions that are able to prepare students to develop the skills needed for 21st century learning. This research uses qualitative methods, namely by searching for data and information whose findings are not obtained through calculations and statistical procedures so that the results are descriptive. Data collection techniques in this research are through observation, interviews, and documentation in the form of written objects such as books, magazines, documents, and so on. The results of this research show that Ma'had Al-Zaytun, which is based on the spirit but modern Islamic boarding school system, instills the skills needed in 21st century learning, including the ability to think critically in dealing with every problem, the ability to think critically, and the ability to think critically. communicate using various languages, the ability to Large Scale Collaboration (KSBB), the ability to produce products (creativity) with the help of computer technology and have a religious character that comes from the Al-Qur'an, the sunnah of Rosul Muhammad SAW, the qualities contained in Asmaul Husna and Asmaun Nabi, as well as the character of nationalism contained in the five foundations of the state (Pancasila), the 1945 Constitution and the national anthem Indonesia Raya 3 Stanza.